(untitled) (Research, Society and Development, 2020)
Failures at urban drainage systems are oftentimes identified at the Brazilian scenario. These problems are related to the intense anthropization of urban areas, misconceptions of projects, and deficiencies of normative guidelines, which are intended to orientate land usage and occupation. In this context, the following article aims to exhibit an evaluation and diagnosis method for consolidated urban drainage systems. In a way that it can enable possible corrective actions, which may guarantee the proper operation of the important basic sanitation axis that the stormwater disposition represents. The method elaboration is complemented by its application to a study area (region Serra Dourada, 3rd stage), highlighting the evaluation design methods, and steps to acquire the data that support them. Those results indicated the insufficient quantity of sewer grates, and under dimensionalized storm sewer pipes for the total effluent flow. These misconceptions led to the system resizing in order to accomplish required specificities that make the pieces of equipment comply with local reality.